Differentiated Development in the School in Particular Motivation - Ágota Szabóné Balogh; Erzsébet Lestyán (Ignatianum University Press, 2019)
One of the main tasks of education is the appropriate motivation of students. The authors present their investigations in the field of learning motivation, which are the elements of significant research; they examine how differentiated education affects learning features. They apply pilot and control groups to follow the effect of differentiated development over the years. One can directly apply their research results into educational practice. This present study focuses on motivation, which is one of the constituents of this research sequence. For the development of these areas, the authors looked for tools that can be used when working with 10-14 year old students, which help to motivate them and raise their interest. The authors raise the issue how and in what manner digital tools are suitable for the motivation.